2018
DOI: 10.1111/eci.12999
|View full text |Cite
|
Sign up to set email alerts
|

Proenkephalin for the early detection of acute kidney injury in hospitalized patients with chronic kidney disease

Abstract: Delta PENK levels improve the early detection of contrast-induced AKI in CKD patients over serial creatinine sampling. Delta PENK accelerates the detection of creatinine-blind AKI by 24 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Therefore the elevated functional markers almost certainly reflect baseline function rather than an early signal of AKI. [33] Rather than an absolute value of proenkephalin as a predictor of AKI a delta value may be of more value particularly where a significant number of patients have CKD [33]. Our results indicate that although the markers of function are predictive of AKI the performance is not as good as that of markers of stress under the conditions tested.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Therefore the elevated functional markers almost certainly reflect baseline function rather than an early signal of AKI. [33] Rather than an absolute value of proenkephalin as a predictor of AKI a delta value may be of more value particularly where a significant number of patients have CKD [33]. Our results indicate that although the markers of function are predictive of AKI the performance is not as good as that of markers of stress under the conditions tested.…”
Section: Discussionmentioning
confidence: 68%
“…Among the functional biomarkers examined in our study, proenkephalin was more recently identified and has been proposed as a more accurate indicator of GFR and AKI than serum creatinine [32]. A recent study examined proenkephalin at baseline and serially after contrast media administration to predict AKI in a population with CKD [33]. Of note, in this group the baseline proenkephalin levels were related to steady-state renal function and the accuracy of detection of subsequent AKI were similar between serum creatinine and proenkephalin in keeping with our observations.…”
Section: Discussionmentioning
confidence: 92%
“…The problem of precocity, although desired, is poorly applied in clinical studies, perhaps due to the difficulty of segmenting serial samples, in addition to the need for intervention with potential renal injury with pre and post collections. In a study evaluating one hundred eleven hospitalized patients with CKD undergoing radiographic contrast procedures, the authors did not find differences in PENK or baseline Scr during the period before contrast, but the PENK delta increased in patients with AKI after use of the PENK contrast on Day 1 (198 pmol/l vs. 121 pmol/l, P < 0.01) [ 26 ]. However, the study by Shan et al [ 27 ], including 92 patients undergoing cardiac surgery, corroborates our findings, and preoperative PENK was an independent predictor of AKI (OR 23.8 (95% CI 2–270), P = 0.011).…”
Section: Discussionmentioning
confidence: 99%
“…Our study compared the standard marker of glomerular filtration Scr with PENK and CYS-C and revealed that PENK detected AKI 48 h earlier than serum creatinine. In the study reported in the previous paragraph in patients with CKD using contrast, the precocity was 24 h with PENK [ 26 ]. Studies [ 28 , 29 ] comparing the PENK value with Scr yielded a correlation r = 0.74 or greater.…”
Section: Discussionmentioning
confidence: 99%
“…Human proenkephalin (PENK) is an endogenous opioid polypeptide hormone. Upon proteolytic cleavage, PENK generates enkephalin peptides, predominantly Met-enkephalin (Met-ENK) and, to a lesser extent, Leu-enkephalin (Leu-ENK) 32,33 . These enkephalin peptides can activate opioid receptors, influencing physiological functions such as pain perception and stress responses 34 .…”
mentioning
confidence: 99%